A novel three dimensional nonlinear tuned mass damper and its application in floating offshore wind turbines. (15th April 2022) - Jahangiri, V.; Sun, C.
Abstract: This paper proposes a novel three-dimensional non-linear tuned mass damper (3d-NTMD) to effectively mitigate three-dimensional structural responses. The 3d-NTMD consists of a mass and three pairs of springs and dash-pots configured in three axes. The resultant restoring forces are nonlinear with respected to the displacements in the three axes. While the proposed 3d-NTMD has the potential to simultaneously mitigate triaxial vibrations, the system nonlinearity complicates the optimization. A numerical search approach is adopted to determine the optimum design. The National Renewable Energy Laboratory spar floating wind turbine (FWT) model is used to evaluate the performance of the 3d-NTMD in reducing the motion of the FWT in three directions: pitch, roll and heave. To this end, an analytical model of a spar FWT with a 3d-NTMD in the spar is established. The wind loading is determined using blade element momentum method and the wave loading is calculated using JONSWAP spectrum and Morison equation. The effectiveness of the 3d-NTMD is examined under operational and parked conditions. Results show that the 3d-NTMD outperforms linear TMDs and can effectively reduce the response of the FWT in three directions. The proposed 3d-NTMD has the potential to mitigate three-dimensional vibrations of a large set of civil/mechanical systems. Highlights: A novel three-dimensional nonlinear tuned mass damper (3d-NTMD) has been proposed. The nonlinear stiffness improves the mitigation effect when compared to traditional linear TMDs. The optimum design of the 3d-NTMD is obtained under symmetric and asymmetric random excitations in three directions. The proposed 3d-NTMD can effectively reduce the structural response of the FWT in heave, pitch, and roll directions.